If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10-5x=3(x-4)-2(x+7
We move all terms to the left:
10-5x-(3(x-4)-2(x+7)=0
| 300-5x=300 | | 6(t+-1)=9(t+-4) | | -52=-4(1-3r) | | Y=-z+1 | | 8p+5=10 | | 6(t+-1)=9(t+-36 | | 6r+8=20 | | 5(v+4)=20 | | a/5+12=12 | | -12+a=6 | | 5/9(x-7)=10 | | a5+12=12 | | 16=2b+8 | | (2x+6)+5x=90 | | 2r+6=16 | | (3x+1)=61 | | 5q-6.5=10.2 | | 4x/7=-8 | | (6x+5)=107 | | 5(3h+6)=5(2h-9) | | 2n=14-2n | | 4(x-10)+13=273 | | -15/4=-5v | | 2|8z+5|=4 | | 7x–8=9x+7 | | 25=-3/5v | | -8(u-8)=-2(u+4) | | 5(8a-7)=-2-3a | | 8m-2(6-4m)=36+8m | | 7*c=728 | | 2+2(x+1)=2x+5 | | -2(-8v-8)=-34+6v |